Strengthening Media Literacy and Public Speaking Competence among Junior High Students through Campus-School Collaboration - Muhammad Ridwan Yunus; Jelita Purnamasari; Ayu Kurnia Utami; Patma Tuasikal; Rahmah Agustiani (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
Adolescents’ high digital media engagement does not automatically translate into communicative competence In the digital communication era, particularly in peripheral regions with limited school resources. This study evaluated the effectiveness of a one-day community service workshop aimed at enhancing public speaking and foundational broadcasting skills among 40 students aged 13–15 at SMP YPPK Biak, Papua. The workshop employed a participatory, experiential learning approach combining explanation, demonstration, guided practice, and peer feedback, facilitated jointly by university lecturers and campus radio practitioners. Data were collected using pre–post tests, structured observation sheets, participatory observation, and satisfaction questionnaires to measure confidence, knowledge, practical skills, and engagement. Results show that students’ confidence in public speaking increased from 33% to 48%, while understanding of articulation, posture, eye contact, and vocal projection rose from 45% to 62%, accompanied by a decrease in visible anxiety from 62% to 49%. Broadcasting knowledge improved from 18% to 71%, with 85% of students demonstrating correct microphone handling, 73% maintaining proper distance, and 68% improving rhythm and pacing during simulations. Over 90% of participants reported the workshop as useful and enjoyable, and teachers observed increased expressiveness and readiness to engage in school–university broadcasting collaborations. These findings indicate that short-term, practice-oriented interventions can effectively develop communication competence, boost confidence, and foster motivation among adolescents, while providing a replicable model for participatory learning and sustainable school-based broadcasting initiatives in resource- limited contexts.